Study on the Drive Characteristic of Roller Chain of the Large Stroke Manipulator System - Hu Yan (Jixie chuandong, 2015)
In order to solve the current problem of the transmission manipulator design of high manufacturing costs and general easy occasions limitations,a new manipulator based on roller chain drive system is presented,and aiming at the roller chain drive system,through the use of multi-body dynamics theory and Lagrangian methods,the transverse vibration modal characteristics and stability of manipulator system roller chain drive is analyzed and got.The results show that,by comparing the operation characteristics of the large stroke with roller chain drive and non-roller chain drive manipulator system,the proposed model has lower manufacturing costs,and the new manipulator system solutions can better solve the limitations of using traditional manipulator problems are generally easy to use the occasion.The manipulator with roller chain drive and non-roller chain drive in the ideal trajectory operating characteristics of small differences,it is meet the general requirements for operation of the manipulator with using less precision.The chain drive transverse vibration natural frequency increase with the decreasing chain length,the drive speed has less affected on transverse vibration,the chain tension on the chain drive transverse vibration shows that the linear relationship between the natural frequency increases as the tension gradually increases.